Reply To The Comments Of Francisco Gómez Camacho - Figueroa, Adolfo (1977)
Reply of Aldo Figueroa, author of “Income Distribution In Peru”, Lima, Instituto de Estudios Peruanos, 1975, to the comments of Francisco Gómez Camacho about the book.